Quantifying the spatio-temporal dynamics and coupling coordination of PLE spaces in Heilongjiang’s Grain Belt: a grid-based geospatial analysis - Ge, Sijia; Ma, Yanji (Frontiers in Ecology and Evolution, 2025)
IntroductionChina’s major grain-producing areas are facing increasingly prominent tensions between grain security and ecological protection. A systematic understanding of the evolution and coordination mechanisms of production–living–ecological (PLE) spaces is essential for promoting efficient land allocation and regional sustainable development.MethodsTaking Heilongjiang Province as a representative case, we constructed a functional classification–evaluation system for PLE spaces using land-use data from 2000, 2010, and 2020. Spatial analysis, land use transfer matrices, coupling coordination models, and gravity center migration methods were applied to assess functional evolution and spatial synergy.Results(1) Production space in the Songnen and Sanjiang plains expanded significantly, primarily through conversion of ecological space; (2) The spatial agglomeration of production space slightly declined (Moran’s I decreased from 0.7567 to 0.7508); (3) Overall coupling coordination steadily improved, though production–living integration remained weak in rural areas; (4) The coupling coordination center of gravity exhibited a “northward-then-southward” shift, reflecting a transition from ecological to agricultural spatial dominance.ConclusionThis research makes three significant contributions: first, by integrating spatiotemporal dynamics with spatial coupling analysis, it systematically decodes the functional transition logic and trade-off mechanisms governing PLE spaces in grain-producing regions; second, it substantiates China’s “Big Food Vision” policy by demonstrating how diversified food sources across forests, grasslands, and aquatic systems can harmonize ecological conservation with sustainable land use; third, it highlights marked regional differentiation in PLE space evolution, showing that while agricultural cores exhibit relatively high coordination, production–living synergy remains suboptimal, necessitating targeted spatial governance interventions.